BOARD'S GREEN TRAINING AND ENVIRONMENTAL PERFORMANCE: A STUDY OF EXTRACTION INDUSTRIES IN INDONESIA - Asni, Nur; Lestari, Kurnia Cahya; Akib, Mulyati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Green training is an educational approach that incorporates environmental themes to promote company sustainability across economic, social, and environmental dimensions. The purpose of this study is to explore the influence that green training conducted by the board of directors, the board of commissioners, and the independent commissioners has on the organization's performance in the environment. It focuses on public corporations listed on the Indonesia Stock Exchange and involved in the mining, quarrying, and oil and gas extraction industries. Panel data analysis with the OLS approach (the pooled OLS model) was conducted on 105 firm-year observations using the STATA MP13 application. The findings indicate that green training substantially and positively impacts the environmental performance of mining, quarrying, and oil and gas extraction companies at each board level. The robustness test performed fits with this finding. Several control variables, namely firm size and return on assets, were found to affect environmental performance, while board size, firm age, leverage, and ownership did not. JEL: M53, O39, Q56.